A review on fall detection systems in bathrooms: challenges and opportunities - Ramanujam, E.; Perumal, Thinagaran; Shankar, K. (Springer, 2024)
The share of the aged population over and above 65 years increased from 6% in 1990 to 9% in 2019. The percentage of the aged population might increase further to 16% by 2050. Due to socio-demographic changes and nuclear family setups, elder people live alone and encounter many issues at home, especially falls, while doing their daily activities. The probability of a fall inside the bathroom is higher than a fall inside the living place due to specific hazards. Various research works have been proposed to monitor people from falls (fall detection systems -FADE) inside the home environment. However, those systems do not concentrate much on fall detection inside the bathrooms (FADEB). Alternatively, we witness certain smart gadgets for the safety of the elders inside the bathroom, which prevents them from a fall by assisting. However, these gadgets are not designed in a way to report the fall. To overview the FADEB systems, electronic databases such as PubMed, Web of Science (WoS), Scopus, Google Scholar, and DBLP were used to fetch the research works published from 2007 to 2023. The FADEB papers are filtered out and critically reviewed in terms of implementation details concerning data collection, feature extraction, and classification. The specific challenges related to FADEB are quoted that need to be addressed in the near future to monitor the falls inside the bathroom.